Blood Lead Exposure and Association With Hepatitis B Core Antibody in the United States: NHANES 2011-2018 - Kexing Han; Tengyao He; Siran Huang; Weijie Sun; Yufeng Gao (Frontiers Media S.A., 2022)
The objective of this project was to explore the distribution and related factors of blood lead and the association between blood lead and hepatitis B core antibody (HBcAb). All the data were from the U.S. National Health and Nutrition Examination Survey (NHANES). In total, 15,097 (aged 20-80 years) participants were included. Participants without a history of blood transfusion were more likely to be exposed to lower levels of blood lead [−2.30 (−3.13, −1.47) for HBcAb (-) and −2.23 (−4.54, 0.08) for HBcAb (+)]. The odds ratio (OR) of HBcAb (+) increased with blood lead and the result was 1.09 (1.06, 1.12). This study showed that older adults, men, people with a lower education level, a lower ratio of family income to poverty (PIR), a lower body mass index (BMI), or a history of blood transfusion, people who lived with a companion or with a total number of people in the family >3, people living in the United States for a longer time, U.S. citizens by birth or naturalization, and people not born in the United States were associated with higher blood lead exposure, and blood lead had a positive association with HBcAb (+).